The Relationship Between Knowledge of Postpartum Mothers About Breast Care With The Effectiveness of Breast Milk Expenditure at Puskesmas Lumban Julu, Toba District, 2023 - Lumbantobing, Pratiwi; Vivi Santri, Yuni; Fithri, Nurhamida (Pena Cendekia Insani, 2023)
In supporting optimal fulfillment of breast milk production for babies, it should be as expected, one of the determining factors in breastfeeding is breast care since pregnancy and after delivery. The purpose of this study was to analyze the relationship between the knowledge of postpartum mothers about breast care and the smooth production of breast milk in postpartum mothers at UPT Puskesmas Lumban Julu, Toba Regency in 2023. The type of research used was analytic observational with a cross sectional design. Sampling used Total Sampling so that a sample of all postpartum mothers at the Lumban Julu Health Center UPT totaled 32 samples. Data analysis used the Chi-Square test. The results of the study of 32 postpartum mothers showed that 15 respondents (46.9%) had good knowledge and experienced smooth breastfeeding, 3 respondents (9.4%) had good knowledge and experienced non-fluent breastfeeding. While respondents with less knowledge and experienced smooth breastfeeding were 5 people (15.6%), and respondents with less knowledge and experienced non-fluent breastfeeding were 14 people (43.8%). Chi-square test results with p-value = 0.006 <? (? = 0.05). The conclusion of this study states that there is a significant relationship between knowledge of breast care and the smoothness of breastfeeding at UPT Puskesmas Lumban Julu, Toba Regency in 2023. Health workers at UPT Puskesmas Lumban Julu are expected to further improve their health promotion regarding the importance of breast care for postpartum mothers in improving the smoothness of breastfeeding so as to improve the quality of health services and quality at the research site.